Analysis of existing problems in the field of parliamentary control over the state budget in Uzbekistan (Global Scientific Review, 2023)
The article analyzes the theoretical and legal foundations of parliamentary consideration of reports on budget execution. For example, in some sources, it is indicated as quality control of the execution of laws, while in others it is analyzed as the legislative activity of the parliament. The experience of developed countries with the CIS countries is also described. The reports submitted to the parliament on the state budget of the CIS member states, including Uzbekistan, were analyzed. It is analyzed that the USA, Brazil, and Japan could change the state budget's main parameters. The discussion and approval by the parliament of the draft state budget - recognition as the subject of legislative activity, was studied, and in turn, the problems associated with this process in our country were identified